Association of Lower Urinary Tract Symptoms and Benign Prostatic Enlargement in Patients with Hypertension - Dicky Stefanus; Safendra Siregar (Majalah Kedokteran Bandung, 2023)
Development of hyperplastic nodules in the transition zone of the prostate is the characteristic of Benign prostatic enlargement (BPE). Men with hypertension have a high risk of severe lower urinary tract syndrome (LUTS). This restrospective cohort analytic study investigated the association between LUTS and BPE in hypertension patients. Subjects were BPE patients with primary hypertension who visited the urology clinic of Dr. Hasan Sadikin General Hospital Bandung that were sampled consecutively from 2017 to 2020. Three hundred and twenty-four patients from the urology department participated in the study. These patients were categorized into  mild LUTS (IPSS 1-7)  (n=37, 11.4%), moderate LUTS (IPSS 8-19) (n=169, 52.2%), and severe LUTS (IPSS 20-35) (n=118, 36.4%). A positive correlation (r = 0.761, p = 0.000) and weak positive correlation (r = 0.152, p = 0.006) were found between systolic blood pressure and prostate volume and between LUTS and systolic blood pressure, respectively. In addition, there was also a weak positive correlation between diastolic blood pressure and prostate volume (r = 0.065, p = 0.245) and LUTS (r = 0.015, p = 0.784). Thus, there is an association between hypertension and prostate enlargement and the severity of lower urinary tract symptoms